Frequency of in-Hospital Survival and Mortality in Stemi Patients Complicated by Cardiogenic Shock: A Retrospective Cohort Study - Huma Naeem Tareen, Salman Ahmed, Muhammad Hamza, Iftikhar Hussain, Jamshed Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: ST-segment elevation myocardial infarction (STEMI) complicated by cardiogenic shock (CS) is a critical condition with high mortality. Despite advances in treatment, including primary percutaneous coronary intervention (PCI), patient outcomes remain suboptimal. Objective: This study aimed to evaluate the clinical characteristics, procedural outcomes, and long-term survival of STEMI patients with CS undergoing primary PCI. Methods: A multicenter retrospective cohort study was conducted on 160 STEMI patients with CS undergoing primary PCI at Niazi Medical and Dental College, Sargodha and Memon Medical Institute Hospital, Karachi between January 2019 and August 2023. Data on baseline demographics, clinical presentation, procedural details, and outcomes were analyzed. The primary endpoint was in-hospital mortality, and secondary endpoints included major adverse cardiac events (MACE) and long-term survival. Results: The cohort’s mean age was 58.2 ± 12.4 years, with 72% male. The in-hospital mortality rate was 34.4%, while MACE occurred in 22.5%. The 3-year survival rate was 62.3%. Logistic regression identified age >65 years, Killip class ≥3, and left ventricular ejection fraction (LVEF) <30% as independent predictors of poor outcomes. Conclusion: Primary PCI in STEMI patients with CS is associated with high mortality. Early identification of high-risk patients and timely intervention are crucial for improving outcomes. Keywords: STEMI, cardiogenic shock, primary PCI, mortality, survival